Estudo sobre a aprendizagem da docência na educação a distância: uma análise da percepção dos professores da UAB-UFSCar - Brito, Nara Dias (2014)
The distance education (DE) is basically characterized by the use of one or more technologies which allow the communication between professors and students geographically separated. The development of digital technologies enables the configuration of the distance education as we know it in the contemporaneity. The courses in this mode, besides using technologies to inform and communicate, such as oral and written languages, also begin to use digital language. In this mode, a new way of organization of the teaching work was idealized, and this, on one hand, produces precariousness of professors work and, on the other hand, provides a collaborative and team work. Considering the peculiarities of DE, the preoccupation is to comprehend how the professor who has experience in classroom education learns to be a professor in the distance mode. The general objective in this research is to analyze the learning process of virtual teaching, taking into account the dilemmas of beginner professors in the distant mode and the knowledge they produced from that experience. The specific objectives are: to verify the dilemmas faced by professors in their first offerings in DE disciplines; to characterize elements of the formation and professional path of the interviewed professors in this mode; to analyze the learning process of virtual teaching; and, at last, to indicate the constructed by the teaching practice in distance mode, which knowledge the teacher must develop to become good teachers in DE and the influence of this knowledge constructed by the practice in DE on regular education. This research is qualitative, and to its realization seven professors who work in undergraduation distance courses in Federal University of São Carlos were interviewed. The main found results were the dilemmas faced by the professors, in the beginning of virtual teaching, are related to planning activities without knowing the DE public and their necessities. Another pointed dilemma was the unfamiliarity when the professors see the end of the process of producing the discipline. It happens because the professor, in DE, counts on the support of professionals in the conception of the discipline and its offer, and this often generates the feeling of loss of authonomy. At last, another dilemma experienced by some professors was the difficulty of managing the working time in DE and of conciliating between working time and the other functions of the professor. The learning of virtual teaching happened, mainly, through the practice and the reflection on the practice. Reflective and learning of virtual teaching processes often happened in a collective way, with tutors. The knowledge learned by teaching experience in DE are related to communicative competence, mainly in regard to written language which is intensely used in the virtual learning environment, to the competence to deal with the technologies and tools available for the development of activities, to the competence of teamwork and to the competence related to planning the discipline, considering the different rhythms of learning of each student, and to anticipation of doubts.